Software Testing and Quality Assurance (Case Study: ColorNote) - Hali Yanto (RISTEC : Research in Information Systems and Technology, 2025)
High-quality software requires a structured testing (software testing) and quality assurance (QA) process to ensure the application functions according to user needs. This study aims to analyze the quality of the ColorNote application, an Android-based note-taking application developed by Social & Mobile, Inc. The testing method used is Black Box Testing with a manual testing approach, which focuses on key functional aspects such as creating and editing notes, setting reminders, Google synchronization, and managing checklists. The test results show that most of ColorNote's features run well and produce output according to expectations. Each test scenario performed produces valid results, indicating that this application has high stability and resolution. However, there are still several minor aspects that can be optimized, such as improving performance and developing additional features to enrich the user experience. The conclusion of this study shows that Black Box Testing-based testing is effective in identifying the suitability of the function and performance of mobile applications. Documentation of these test results can be a reference for developers in efforts to improve software quality, as well as strengthen user confidence in the developed application.